Proses Berpikir Kreatif Siswa dalam Memecahkan Masalah Trigonometri Berdasarkan Gaya Kognitif - Putera, Ahmad Junaidi Hutama; Ismail, Ismail; Wijayanti, Pradnyo (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The research is a qualitative descriptive study which aims to describe students' creative thinking processes in solving trigonometry problems based on cognitive style. The data collection method uses the GEFT test to determine students' cognitive styles, problem solving tasks using trigonometry material and interview guides to determine students' creative thinking processes. The research subjects consisted of two class X high school students with different cognitive styles, namely field independent and field dependent with both students being male. The research results of students with field independent and field dependent cognitive styles fulfill each step or stage of the creative thinking process in solving trigonometry problems. In the problem solving process there are differences in choosing the ideas used to solve the problem.